SOSIALISASI PELAKSANAAN SADARI UPAYA DETEKSI DINI KANKER PAYUDARA - Metha Fahriani; Ruri Maiseptya Sari; Yuni Ramadhaniati (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2021)
Background : Breast cancer is the second most common cancer in the world and is the most common cancer in women with an estimated 1.67 million new cancer cases diagnosed in 2012 (25% of all cancers). According to data from the World Health Organization (WHO), the incidence of cancer increased from 12.7 million cases in 2011 to 14.1 million cases in 2017, while the number of deaths increased from 7.6 million people in 2011 to 8.2 million in 2017. 2017 (WHO, 2018).The main problem with breast cancer is irregularity and it is rare to do a breast self-examination (BSE) correctly. The implementation of BSE activities for all women starts from the childbearing age, because 85% of breast abnormalities are actually discovered by the patient for the first time if there is no mass screening. Purpose : The purpose of this community service is to increase public knowledge, especially women of childbearing age about the importance of early detection of breast cancer through Breast Self-Examination (BSE). Method : The target of community service is 28 women of childbearing age in Kembang Mumpo Village, South Bengkulu Regency. This service begins with health socialization about the importance of doing Breast Self-Examination (BSE) using leaflets and booklets as well as direct presentation of the material, then continued with the practice of how to do BSE correctly. Result : The result of community service was an increase in knowledge by 69% from before socialization to after socialization was given. The final result after the practice of doing BSE. Conclusion: The conclusion is there is an increase in the knowledge and motivation of target women of childbearing age (WUS) to perform Breast Self-Examination (BSE). Where the target of WUS has begun to understand how important BSE behavior is as an early detection effort to prevent breast cancer, namely by continuing to live a healthy lifestyle and have a high awareness of doing BSE examinations